KESESUAIAN KEMAMPUAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT DENGAN STANDARD OPERATING PROCEDURE PADA PELAYANAN RAWAT JALAN DIRUMAH SAKIT PUSAT ANGKATAN UDARA DR. S. HARDJOLUKITO YOGYAKARTA - , SITI MUKMINATUL K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : RSPAU dr. S. Hardjolukito now focus in increasing service quality, one of the progress is SIMRS. Since end of 2012, the first SIMRS development was applied. When the development on progress, problem found about the hospital information system of ambulatory care services. Because of the problem, observer want to discover the SIMRS of ambulatory care RSPAU dr. S. Hardjolukito Yogyakarta between the technology capability of SIMRS and user so that this computer program applicable with job description. Goal: to discover the detail of job description in the hospital,to discover the funcion of SIMRS in ambulatory care system, and to discover compatibility between job description user with the capability of SIMRS especially for ambulatory care services in RSPAU dr. S. Hardjolukito Yogyakarta. Method : this observation method is descriptive using qualitative approach based on case study, with cross-sectional experimental design. subject in this observation are 4 registration staff, 1polyclinic staff, 3 laboratorium staff, 2 cashier, and 1 staff of EDP, however the object of this observation is SIMRS computer program for ambulatory care services. the data collecting method is using observation and interview Result: implementation of job description in ambulatory care system with the standard operating procedure, therefore some of job description not complete yet about daily sensus by polyclinic staff. Uncompatibility found between job description and the funcion of SIMRS which are hospital patient card printing and informing schedule by doctor. Another problem found in polyclinic division, which is about the disability of SIMRS in inputing anamnesa, sending medicine recipe to drugstore (pharmacy), and making a report. In the laboratory, SIMRS disability found when inputing master standart and making a report. In cashier, SIMRS disability found when making a report. The conformity of SIMRS wih job description is 60%.